Molecular expression and characterization of Taenia solium TS14 gene for sensitive detection of porcine cysticercosis - JOSHI, CHITRA; SARAVANAN, B C; MANJUNATHACHAR, H V; SANKAR, M; SARAVANAN, R; GAUTAM, S; TEWARI, A K (The Indian Journal of Animal Sciences, 2016)
In the present study, molecular expression and characterization of TS14 gene of Taenia solium (Indian isolate) was carried out for sero-prevalence study of porcine cysticercosis. The complete open reading frame (ORF) of TS14 gene was amplified by RT-PCR from mRNA isolated from T. solium cysticerci (Indian isolate). The amplicon was cloned into the pET-32a(+) expression vector and used to transform Escherichia coli BL21 codon(+) cells to produce TS14 antigen. The nucleotide and deduced amino acid sequences of the TS14 were aligned against the related sequences of T. solium available in public domain for in silico analysis by DNA STAR and MEGA version 4.0 softwares. The nucleotide sequence revealed that the TS14 gene of T. solium (Indian isolate) encodes 85 amino acids and its nucleotide sequence had 98.8% to 99.5% sequence homology with that of China, Peru and Mexico isolates. A high-level expression of the recombinant protein was observed in the molecular range (Mr) of 29 kDa. The rTS14 was confirmed by its specific immunoreactivity against hyper-immune and known reference positive pig sera (8). The protein was serologically non-reactive to known cysticercus negative pig sera samples and further lacks cross-reactivity against hydatid cyst positive pig sera. The present preliminary investigation revealed the good potential of rTS14 for serodiagnosis of T. solium cysticercosis.